2019
DOI: 10.1016/j.dcn.2019.100728
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of age and BMI are related to altered cortical thickness in adolescence and adulthood

Abstract: HighlightsAn age-by-BMI interaction related to altered cortical thickness across development.In adolescents, greater BMI Z-score for age was associated with greater thickness.In adults, greater BMI for age was associated with reduced thickness.Delay discounting related to reduced frontal thickness in high-BMI individuals.The study of adolescent brain development should consider adiposity effects.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 84 publications
(100 reference statements)
2
15
0
Order By: Relevance
“…Lou et al (2014) showed greater GMVs within the bilateral putamen compared with the control group [44]. However, two studies showed that a higher BMI was associated with a lower GMV within the bilateral putamen [49] and left putamen [54]. Taki et al (2008) showed a negative correlation between the BMI and the GMV and the gray matter ratio (percentage of GMV in the intracranial volume) within all lobes, the anterior cerebellum and the midbrain and a positive correlation within regions of the frontal and temporal lobes, posterior cerebellum, thalami and caudate heads in men (no significant association was described in women) [57], and another study found that there was no significant association between the BMI and brain volumes (measured by total brain volume and GMV) [61].…”
Section: Cross-sectional Designmentioning
confidence: 83%
See 4 more Smart Citations
“…Lou et al (2014) showed greater GMVs within the bilateral putamen compared with the control group [44]. However, two studies showed that a higher BMI was associated with a lower GMV within the bilateral putamen [49] and left putamen [54]. Taki et al (2008) showed a negative correlation between the BMI and the GMV and the gray matter ratio (percentage of GMV in the intracranial volume) within all lobes, the anterior cerebellum and the midbrain and a positive correlation within regions of the frontal and temporal lobes, posterior cerebellum, thalami and caudate heads in men (no significant association was described in women) [57], and another study found that there was no significant association between the BMI and brain volumes (measured by total brain volume and GMV) [61].…”
Section: Cross-sectional Designmentioning
confidence: 83%
“…As shown in Table 1, the publications were released between July 2006 and February 2021, and the sample size in each study varied from 32 to 2344 participants. A total of 11 studies had samples exclusively comprised of healthy participants [7,22,[41][42][43][44][45][46][47][48], and two studies included a healthy subgroup [49,50]. The main characteristics of the participants are shown under "Sample Size, Type of Groups" in the table.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations